2020
DOI: 10.37043/jura.2020.12.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Towards Green Resilient Cities in Eastern European Union Countries

Abstract: Investing in green facilities is a process of urban renewal that can transform cities by enhancing the quality of life, strengthening the local economy and reducing environmental impact. Nevertheless, greener cities are not a guarantee for improved adaptive capacity when facing current local or global challenges. In this context, we have taken into account a series of sample cities from Central and Eastern European Union. Using the green cities typology proposed by the European Environment Agency, the present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…(3) The per-capita GDP and the urbanization level can reflect the degree of a city's economic growth, which can significantly boost the urban resilience. The higher a city's economic growth level, the stronger the urban resilience, which is consistent with the research in the literature [55][56][57]. The resilience theory stresses the entire economic and social environment's ability to adapt to and recover from risks [58].…”
Section: Influence Factor Analysissupporting
confidence: 85%
“…(3) The per-capita GDP and the urbanization level can reflect the degree of a city's economic growth, which can significantly boost the urban resilience. The higher a city's economic growth level, the stronger the urban resilience, which is consistent with the research in the literature [55][56][57]. The resilience theory stresses the entire economic and social environment's ability to adapt to and recover from risks [58].…”
Section: Influence Factor Analysissupporting
confidence: 85%
“…There have been numerous publications related to sustainability in the region, with the application of various environmental indicators being relatively popular. For instance, Bănică, A. et al (2020) examined several Central and Eastern European cities to explore the connections between green infrastructure, resilience, and adaptability. Similarly, Csete, Á.K.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, this essay develops an evaluation index system based on three factors: economic resilience, social inclusive resilience, and ecological environment resilience. The existing literature on the factors influencing urban inclusive green resilience focuses primarily on urban development activities [11,12], and there is still potential to investigate other aspects impacting inclusive green resilience capability. Furthermore, although a large number of scholars have confirmed that environmental policies have a positive influence on the level of urban inclusive green development through qualitative and quantitative analyses, there is still a research gap in exploring the impact of environmental policies on inclusive green resilience capacity.…”
Section: Introductionmentioning
confidence: 99%